Analysis Of Education About Early Mpasi With Video Media On The Attitudes Of Early Asi Complete Foods For Mothers Who Have Babies Age 0-6 Months At The Al-Kautsar Prambon Clinic, Sidoarjo District - Attik Fitrian Diyanti (Universitas STRADA Indonesia, 2025)
Toddlers aged 0-6 months need energy and nutrition starting to exceed what is provided by breast milk as a complementary food. In Indonesia, stunting has increased dramatically in 6 month old babies where providing appropriate MPASI can prevent disease and provide good care for babies. MPASI can also help optimal growth and development and prevent stunting or micronutrient deficiencies. This study aims to determine the effect of education about early MPASI using video media on attitudes towards giving early complementary foods to mothers who have babies aged 0-6 months. The research method is pre-experimental design research. The research design uses One-Group Pretest-Posttest Design. The sample used was 30 mothers who had babies aged 0-6 months who came to the Al Kautsar Prambon Sidoarjo Clinic. The sample was determined using the Accidental Sampling technique. The instrument is using a questionnaire. The data collection technique in this research is using the t test. The results of this research are that Ho is rejected and Ha is accepted if tcount > ttable or 16.936 > 1.699 or 0.000 < 0.05. So there is an influence of providing education about early MPASI using video media on the attitude of giving complementary breast milk to mothers who have babies aged 0-6 months. For the results of the questionnaire to determine the respondents' attitudes, there is an overall percentage of 80%, so it can be categorized as good. From the results of this research, it can be used as knowledge for mothers who have toddlers aged 0-6 months that early MPASI is very important for the growth and development of toddlers.